Examining the adoption of chatgpt technology among academics in higher education institutions in malaysia - Au, Weng Chee (2023)
This research investigates the adoption of ChatGPT technology among academics in Malaysian higher education institutions (HEIs), focusing on factors influencing their decisions. Utilizing a robust survey instrument, the study explores the role of facilitating conditions, perceived trust, performance expectancy, and effort expectancy in shaping adoption patterns. Reliability analyses confirm the consistency of the survey, ensuring the credibility of the collected data. Comprehensive demographic profiling offers insights into the diverse academic landscape, emphasizing the need for tailored adoption strategies. Correlation analyses reveal intricate relationships between variables, highlighting the significance of supportive environments and trust in technology adoption. This quantitative study employs SPSS software to explore the adoption patterns of ChatGPT technology within Malaysian HEIs. Utilizing a structured survey instrument, the research investigates the impact of facilitating conditions, perceived trust, performance expectancy, and effort expectancy on academics' adoption decisions. From rigorous reliability analyses, the survey's consistency and stability are verified, ensuring the reliability of the collected data. The study's findings underscore the importance of institutional support, ethical awareness initiatives, and comprehensive policies to facilitate responsible ChatGPT integration. This research provides a foundational understanding of ChatGPT adoption in Malaysian academia, offering valuable insights for future research, policymaking, and educational practices. Keyword: ChatGPT technology, adoption, higher education institutions, facilitating conditions, perceived trust, performance expectancy, technology integration, academic attitudes, ethical awareness, Malaysia.